POLICY EVALUATION OF VILLAGE FUND ALLOCATIONS INIMPROVING THE IMPLEMENTATION OF VILLAGE INFRASTRUCTURE DEVELOPMENT IN TELAGA DISTRICT GORONTALO REGENCY - Anis Naki; Warno Panigoro; Erwin Sunge (Governance: Jurnal Ilmu Administrasi Publik, 2022)
This study is carried out with the aim of analysing exploration and describing things related to rural funding policy in improving the implementation of rural infrastructure development. This study uses a descriptive type of qualitative approach. The focus of research is knowledge, skills, behavior. Research has shown that the evaluation of ADD policy in improving the implementation of SDM infrastructure development, accounting, and public participation are still not optimal in line with its definition. The impediment to ADD policy implementation is in terms of data accessibility, government rules, and communication and planning synchronisation. It is suggested that the village government should further optimise ADD policies to improve the quality of village sdm, energy operators, improve public certification, and accountability reports and access through any media. and the village government had to propose an increase in the ADD budget so that rural infrastructure could continue to play a role in improving public security.